Development Strategy of Subak for Supporting Agroecotourism Empowerment - Suamba, Ketut (Advances in Social Sciences Research Journal, 2015)
Subak is a traditional irrigation system which has local knowledge society that has been inherited from generation to generation. Local knowledge in the form of socio-cultural activities can be used as a strong binder in subak system. Local knowledge also can be used as agroecotourism empowerment. On the other hand, the development of Bali as one of the major tourist destinations in Indonesia, both positive and negative impacts. One of the negative impacts are reduced wetland phenomenon occurs due to land conversion. One way in conservation efforts is by making subak has a role in “Subak Development Strategy for Supporting Agroecotourism Empowerment”. This requires the study objective of this study was (i) identify the strengths, weaknesses, opportunities, and threats in the SWOT analysis method to be able to develop agroecotourism empowerment, and (ii) formulate strategies needed by Subak in preparing developing utilization of agroecotourism empowerment. The study was conducted at the Subak Wangaya Betan, Penebel, Tabanan and Subak Lodtunduh, Ubud, Gianyar. The results of the analysis of internal and external factors after taking into account the weight and rating, at each subak sample resulted in a score for determining the development strategy of agroecotourism in subak system. In Subak Lodtunduh obtained internal factor is the total value of 47.5 and the value of the external factors is 20. At Wangaya Subak Betan obtained internal factor is the total value of 11.5 and the value of the external factors is 24 score of the final results of internal and external factors included in the diagram to obtain the location of the chosen strategy to develop agroecotourism in subak is concerned. In the results obtained Subak Lodtunduh, Subak development strategy on aggressive quadrant. Thereby also the Subak Betan Wangaya, Subak development strategy is obtained in aggressive quadrant. Thus the efforts needed to be more aggressive in the development of the agroecotourism subak system.